The Relationship Between Retinal Nerve Fiber Layer Thickness and Clinical Symptoms of Alzheimer's Disease - Lian, Teng-hong; Jin, Zhao; Qu, Yuan-zhen; Guo, Peng; Guan, Hui-ying; Zhang, Wei-jiao; Ding, Du-yu; Li, Da-ning; Li, Li-xia; Wang, Xiao-min; Zhang, Wei (Frontiers in Aging Neuroscience, 2021)
Background To investigate the relationships between the retinal nerve fiber layer thickness and clinical symptoms of Alzheimer’s disease. Methods In this study, total 96 of AD patients were included and retinal nerve fiber layer (RNFL) thickness (RT) was measured by optical coherence tomography (OCT). Demographic variables, RT and clinical symptoms were compared between the normal and abnormal RT of AD patients (AD-RT). Clinical symptoms, including cognitive, and neuropsychiatric symptoms and activities of daily living (ADL), were evaluated by a series of rating scales. Results The relationship of RT and scores of cognitive symptoms were analyzed in AD patients.54.4% of AD patients have reduced RT. The average RT, RT of superior 1/2 quadrant and RT of inferior 1/2 quadrant of both eyes were all significantly decreased in abnormal AD-RT group (P＜0.001). They also have overall cognitive function and multiple cognitive domains, including memory, language, attention and executive function, significantly impaired (P＜0.05). The thinner the RT, the worse the global cognitive function and multiple cognitive domains. ADL is dramatically compromised in AD patients with reduced RT (P＜0.05). Conclusions The thinner RT may be more correlated with cognitive levels. RT may be an indicator of cognitive decline in AD patients.